Possibilities of dissemination of specialist knowledge and acting capacity in the field of child protection in medicine: a qualitative survey - Maier, Anna (GMS J Med Educ, 2020)
Objective: The shortage of skilled workers and overloaded schedules make further training of health professionals difficult. In addition, child protection is not a systematic part of medical studies. The evaluation of an online course on child protection in medicine reveals positive feedback but also that the main reason for participants aborting the course is lack of time. Dissemination, as an active, targeted spreading of knowledge, can help to further spread knowledge about child protection in the target group. The aim of this article is to investigate whether and how the contents of the online course can be disseminated by professionals who have completed the online course. Methodology: The data were collected through a quantitative online evaluation and qualitative telephone interviews with doctors who had completed the online course and evaluated it using an interpretive-reductive analysis. Results: The respondents consider the need for further training and dissemination measures on the topic of child protection in medicine to be high. However, lack of time and insufficient relevance of the topic would present obstacles in the implementation of such measures. Meaningfulness and time off work or remuneration would in turn create incentives for implementation. Participants in dissemination measures could be motivated for example by further education points. In addition we were able to identify possible approaches for the implementation of such measures. Conclusion: Various parameters influence the motivation of doctors regarding the implementation/perception of dissemination measures. Based on these, recommendations for action are given for different areas of the health care system, such as supplementing the training curricula and providing ready-made materials for dissemination.